La comercialización de la vestimenta indígena de la microempresa Kinku y el posicionamiento en el mercado de Riobamba. - Cuji Guambo, Edith Nathaly (2023)
Every business has the need to have a marketing plan, because it is the most effective way to mark the path of success of the positioning of a brand, understanding that all paths must be based on the mission and vision of the company so that it is fulfilled. its objectives. The investigation is segmented by chapters, the first chapter includes the inductive part of the work, problem statement and objectives that will give the light that this research work must follow to solve the problem raised. In the second and third chapter all the theoretical foundation is available, that is to say, all which includes the state of the art of this research, counteracting the information to work more clearly in the performance of this degree work, which will enrich the marketing process and the level of positioning of the products within the company. The fourth chapter includes the methodology, here the method, type, design of the research, the data collection tools that will give us the opportunity to analyze and interpret the results. The fifth chapter corresponds to the conclusions and recommendations that were reached in this work, with a direct connection to the two other objectives of the contribution of a proposal that will help the company to position itself within the local market